2013
DOI: 10.1016/j.clgc.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

A Gap in Disease-Specific Survival Between Younger and Older Adults With De Novo Metastatic Renal Cell Carcinoma: Results of a SEER Database Analysis

Abstract: Through an analysis of the Surveillance, Epidemiology, and End Results (SEER) registry, we demonstrate that disease-specific survival (DSS) appears to be inferior in older adults with metastatic renal cell carcinoma (mRCC) compared with younger adults. We further suggest that although DSS has improved for younger patients during the era of targeted therapies, a similar improvement is not seen among older adults. Background Consistent with other data sets, our own institutional series suggests that survival in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…When performing a multivariate analysis, large tumor (>120 mm) and older age (>75 years old) were confirmed to be risk factors. These findings align with the earlier outcomes reported by Nelson et al [ 26 ]. In contrast, a meta-analysis examining the predictability of benign kidney tumor revealed that age did not emerge as a standalone predictor [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…When performing a multivariate analysis, large tumor (>120 mm) and older age (>75 years old) were confirmed to be risk factors. These findings align with the earlier outcomes reported by Nelson et al [ 26 ]. In contrast, a meta-analysis examining the predictability of benign kidney tumor revealed that age did not emerge as a standalone predictor [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…A similar trend was reported for elderly patients (⩾70 years) receiving sorafenib ( Eisen et al , 2008 ), raising the possibility that elderly patients with RCC may be more responsive to anti-angiogenic therapy; although, in our analysis, IFN- α -treated elderly patients also seemed to benefit more than younger ones from treatment (median PFS 7.9 vs 5.0 months). These studies, however, contradict a recently reported retrospective analysis of the Surveillance, Epidemiology, and End Results (SEER) registry in which disease-specific survival was inferior in older adults (⩾75 years) with metastatic RCC ( Nelson et al , 2013 ); also, in contrast to younger patients, older patients in the SEER analysis did not experience an improvement in survival in the ‘targeted therapy era' (2005–2009) relative to the ‘cytokine era' (1992–2004). Of note, however, this analysis did not report comorbidity data that may have confounded the results; only patients with de novo metastatic disease and thus inherently intermediate- or poor-risk disease were included.…”
Section: Discussionmentioning
confidence: 64%
“…The current FDA approved targeted therapy drugs for RCC which are the tyrosine kinase inhibitors (sunitinib, sorafenib, pazopanib, and axitinib), monoclonal antibody to VEGF (bevacizumab), and the mTOR inhibitors (temsirolimus and everolimus) [ 45 ]. Targeted therapy has improved treatment outcome as the overall and cancer specific survival of metastatic RCC patients has improved in the targeted therapy era compared to the immunotherapy era [ 46 , 47 ].…”
Section: Clear Cell Renal Cell Carcinoma (Ccrcc)mentioning
confidence: 99%